Prognostic Implication of a Cuproptosis-Related miRNA Signature in Hepatocellular Carcinoma. (13th September 2022) - Jin, Ze; Wang, Mengmeng; Meng, Yajun; Chen, Di; Xu, Yushuang; Jiang, Xin; Xiong, Zhifan
Abstract : Background. Hepatocellular carcinoma (HCC) is one of the most frequently diagnosed malignancies globally, accounting for the third cause of cancer mortality. Cuproptosis, a copper-induced cell death, was recently reported in Science . The purpose of this study was to evaluate the prognostic implication of cuproptosis-related miRNAs (CRMs) in HCC. Methods. Transcriptomic data and clinicopathological features of patients with HCC were extracted from the Cancer Genome Atlas (TCGA) database. Prognostic CRM signature was established by utilizing univariate Cox regression and LASSO analyses. To validate the accuracy of prediction, the Kaplan-Meier (K-M) and time-dependent receiver operating characteristic (ROC) analyses were adopted. A nomogram comprising clinical characteristics and the miRNA signature was developed to improve the prediction of patient outcomes. Finally, functional enrichment analysis and immune infiltration analysis were carried out. Results. Of CRMs, 14 were obtained to construct a prognostic miRNA signature. This CRM signature was an independent factor for predicting overall survival (OS). Kaplan-Meier curves demonstrated a noteworthy difference in survival rates between different risk subgroups (p < 0.001 ). The robust prognostic capacity of this signature was exhibited by sampling verification and stratified survival analysis. Functional analysis indicated that the high-risk group was mainly enriched in signaling pathways and different levels of immune infiltration were revealed between the two risk groups. The potential interaction of the model with the immune checkpoint activities was also detected. Conclusion. The CRM signature could act as an independent predictor to guide individual treatment strategies, which could provide fundamental insights for further studies.